Effect of Increasing Stocking Density on Performance and Heterophil/Lymphocyte Ratios in Broilers - Kuan, K. K.; Adnan, S.; Ramlah, H. (1990)
An experiment on space allowance of 0.095, 0.071, 0.057 and 0.048 m2/bird on wire mesh cages was conducted to study their effects on live-weight, feed intake and feed conversion of Orgal broilers from the age of 4 to 10 weeks. Heterophil/lymphocyte (H/L) ratio,an indicator of stress was also studied to determine whether over-crowding would effect this ratio. During the first 2 weeks of the experiment increasing stocking is reduced feed intake and improve feed conversion without significantly affecting growth rate. Overall, birds on the most liberal floor space allowance (0.095 m2/bird) had the best growth rate (39.2 glda») but this was achieved at a significantly higher feed intake (127.9 g/day) and poorer feed conversion (3.3).Conversely, birds on the highest stocking density (0.048 ,rz2lbiTd) had the poorest performance in terms of growlh rate (32.2 g/day) and feed intake(90.6 g/day). Birds on the two higher stocking density were constantly under stress as indicated by their relatively high H/L. ratios from the fourth week, of the study onwards, these two treatments also had higher mortalities. The results of the present study showed that stress associated with overcrowding reduced performance in broilers. A space allowance of 0.071 m2/bird is sufficient under om- local conditions for broiled reared in raised floor cages.